SYNTHESIS AND SPECTROSCOPY STUDIES OF SOME TRIVALENT METAL IONS COMPLEXES WITH A NEW MACROCYLIC TRIDENTATE LIGAND ETHYL 2-[(1E, 2E) - 2- (HYDROXYIMINO) -1- PHENYL ETHYLIDENE] AMINO - 4,5,6,7 TETRAHYDRO-1-BENZOTHIOPHENE-3-CARBOXYLATE AND THEIR ANTIMICROB - ARUNA K.; SAKINA BOOTWALA (International Journal of Pharma and Bio Sciences, 2012)
Complexes of general formula [M(L)Cl2(H2O)] where M= chromium(III), iron(III) and ruthenium(III), L=ethyl 2-[(1E,2E)-2-(hydroxyimino)-1-phenyl ethylidene] amino-4,5,6,7 tetrahydro-1-benzothiophene-3-carboxylate have been prepared. Complexes were characterized by analytical analysis and physical-chemical methods. The ligand behaves as a tridentate chelating agent and bonded to the metal ion through azomethine nitrogen, ester carbonyl and oximino oxygen atom. Electronic spectra and magnetic susceptibility measurement reveals octahedral geometry. The complexes are found to be non-electrolytic in nature on the basis of low molar conductance. The Ru (III) metal complex exhibited antibacterial activity against drug resistant gram negative uropathogens and antifungal activity.